KETANGGUHAN MAHASISWA YANG BERWIRAUSAHA: STUDI KASUS - Sabela, Osi Isna; Ariati, Jati; Setyawan, Imam (Jurnal Psikologi, 2014)
AbstractHardiness is a character that can influence how individual views their stress and determines an efefctive response towards stress. This study aims to explore the hardiness of college students who were also enterpreneurs. This study used a qualitative-case study method that applied observation and interview methods to collect data. Two undergraduate students joined the study. They started their businesses since they were a freshman and their bussinesses were still well-maintained until the time of study. The results showed that hardiness plays important role in dealing with stressful events due to their double roles as a student as well as an enterpreneur. These enterpreneur students could apply effective coping strategies to solve various problems. Hardiness enables individual to have opportunities to control their lives, to be more energic and enthusiastic, to be more involved in all things they do, and believes that they are ebale to make changes in a positive ways. Hardiness convinced these enterpreneur students to take enterpreneurship as their life path and encouraged them to make efforts to grow their businesses.